Fibrillary Glomerulopathy with a High Level of Myeloperoxidase-ANCA: A Case Report - Tomohiko Asakawa; Mea Asou; Shigeo Hara; Takashi Ehara; Makoto Araki (Case Reports in Nephrology)
An elderly woman was admitted with the chief complaint of gross hematuria. Laboratory values indicated a high myeloperoxidase-ANCA level. In renal histological examination, 40% of the glomeruli showed crescent formation, but immunofluorescence staining showed positivity for IgG, C3, and C1q. Furthermore, the deposition of fibrils in the glomerulus was noted on electron microscopy, and immunohistochemical staining showed strong positivity for DNA-J heat shock protein family member B9 (DNAJB9). Crescent formation is a common feature of fibrillary glomerulonephritis (FGN). Thus, in ANCA-positive crescentic glomerulonephritis, immunohistochemical assessments for immunoglobulins and DNAJB9, as well as electron microscopy, are important to correctly diagnose FGN.